What a trip, Amber Brown - Danziger, Paula, 1944-; Ross, Tony (New York : G.P. Putnam's Sons, 2001)
Amber Brown and her parents go to the Poconos for two weeks with Amber's best friend, Justin, and his family.
250
Keywords: Vacations -- Fiction